Antibacterial and Antibiofilm Potency of XF Drugs, Impact of Photodynamic Activation and Synergy With Antibiotics - Board-Davies, Emma Louise; Rhys-Williams, William; Hynes, Daniel; Williams, David; Farnell, Damian Joseph John; Love, William (Frontiers in Cellular and Infection Microbiology, 2022)
With increasing incidence of antimicrobial resistance, there is an urgent need for novel and effective antibacterials. Destiny Pharma plc have developed a series of porphyrin-based XF drugs, some with dual mechanisms of antibacterial action. An innate mechanism acts through binding to the outer bacterial membrane and a separate, light-activated, photodynamic (PD) mechanism, acts via the generation of reactive oxygen species. This study aimed to assess the innate and PD associated antibacterial activity of XF drugs against planktonic bacteria, their biofilms and combinational effects with conventional antibiotics. Minimum inhibitory concentrations (MICs) were determined for 3 XF drugs against 114 bacterial isolates. MICs for XF-73 and XF-70 were determined (± PD). DPD-207 was designed to not exhibit PD action due to its structure. XF-drugs (± PD) were further assessed for synergy with conventional antibiotics (using a checkerboard assay) and antibiofilm activity against susceptible strains. XF drugs were innately active against all tested Gram-positive isolates. PD action significantly increased bacterial susceptibility to XF-73 and XF-70 for all Gram-positive isolates. Generally, the XF drugs exhibited higher MICs against Gram-negative isolates, however PD significantly enhanced potency, particularly for XF-70. XF-73 and XF-70 exhibited synergy with ertapenem against a methicillin resistant Staphylococcus aureus (MRSA) strain (± PD) and XF-73 with polymyxin B (± PD) against Pseudomonas aeruginosa. No antagonism was seen between the XF drugs and any of the 5 antibiotics tested. The antibiofilm effect of XF drugs was also observed for all Staphylococcus isolates tested. Generally, PD did not enhance activity for other bacterial isolates tested with the exception of XF-73 against Acinetobacter baumannii biofilms. XF drugs exhibited significant antimicrobial activity against Gram-positive bacteria, with PD enhancement of bacterial susceptibility. Additionally, XF drugs displayed synergy with conventional antibiotics and demonstrated antibiofilm effects.